Computational modeling of the bat HKU4 coronavirus 3CLpro inhibitors as a tool for the development of antivirals against the emerging Middle East respiratory syndrome (MERS) coronavirus. Issue 11 (13th June 2017) - Abuhammad, Areej; Al‐Aqtash, Rua'a A.; Anson, Brandon J.; Mesecar, Andrew D.; Taha, Mutasem O.
Abstract: The Middle East respiratory syndrome coronavirus (MERS‐CoV) is an emerging virus that poses a major challenge to clinical management. The 3C‐like protease (3CL pro ) is essential for viral replication and thus represents a potential target for antiviral drug development. Presently, very few data are available on MERS‐CoV 3CL pro inhibition by small molecules. We conducted extensive exploration of the pharmacophoric space of a recently identified set of peptidomimetic inhibitors of the bat HKU4‐CoV 3CL pro . HKU4‐CoV 3CL pro shares high sequence identity (81%) with the MERS‐CoV enzyme and thus represents a potential surrogate model for anti‐MERS drug discovery. We used 2 well‐established methods: Quantitative structure‐activity relationship (QSAR)‐guided modeling and docking‐based comparative intermolecular contacts analysis. The established pharmacophore models highlight structural features needed for ligand recognition and revealed important binding‐pocket regions involved in 3CL pro ‐ligand interactions. The best models were used as 3D queries to screen the National Cancer Institute database for novel nonpeptidomimetic 3CL pro inhibitors. The identified hits were tested for HKU4‐CoV and MERS‐CoV 3CL pro inhibition. Two hits, which share the phenylsulfonamide fragment, showed moderate inhibitory activity against the MERS‐CoV 3CL pro and represent a potential starting point for the development of novel anti‐MERS agents. To the best of our knowledge, this is the first pharmacophore modeling study supported by in vitro validation on the MERS‐CoV 3CL pro . Highlights: MERS‐CoV is an emerging virus that is closely related to the bat HKU4‐CoV. 3CL pro is a potential drug target for coronavirus infection. HKU4‐CoV 3CL pro is a useful surrogate model for the identification of MERS‐CoV 3CL pro enzyme inhibitors. dbCICA is a very robust modeling method for hit identification. The phenylsulfonamide scaffold represents a potential starting point for MERS coronavirus 3CL pro inhibitors development. Abstract : 3CL pro has been proposed as a potential target for the treatment of MERS‐CoV infection. The bat HKU4‐CoV 3CL pro has been exploited as a model for MERS‐CoV 3CL pro (81% sequence identity). We explored the pharmacophoric space of a set of peptidomimetic inhibitors of HKU4‐CoV 3CL pro . The established pharmacophores highlight structural features needed for ligand recognition and were used as 3D queries to screen the NCI database for novel nonpeptidomimetic 3CL pro inhibitors. The identified hits were tested for HKU4‐CoV and MERS‐CoV 3CL pro inhibition.